CHEMICAL CHARACTERIZATION AND DETERGENT POTENTIAL OF CHELIDONIUM MAJUS EXTRACTS - BECZE, Anca; SIMEDRU, Dorina; BÎLTEANU, Liviu; UIUIU, Paul (Studia Universitatis Babeș-Bolyai Chemia, 2025)
The present study investigates the impact of different extraction methods—accelerated solvent extraction (ASE), ultrasound-assisted extraction (UAE), and maceration on the yield, phytochemical composition, antioxidant activity, and antimicrobial potential of Chelidonium majus extracts. ASE demonstrated the highest extraction yield (85.7%) and alkaloid content (5.4 mg AE/ml), correlating with enhanced antimicrobial activity against Escherichia coli, Staphylococcus aureus, and Candida albicans (lowest MIC values: 3.12%, 2.50%, and 6.25%, respectively). UAE resulted in the highest polyphenol content (15.2 mg GAE/ml) and antioxidant capacity (12.8 ± 1.5 µmol Trolox/ml), suggesting its effectiveness in preserving antioxidant compounds. Maceration produced the lowest bioactive compound yield and biological activity. These findings indicate that ASE is optimal for antimicrobial applications, while UAE is preferable for antioxidant-enriched extracts. The results provide valuable insights for optimizing C. majus extraction in pharmaceutical, food, and cosmetic formulations.